2016
DOI: 10.5625/lar.2016.32.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the response using ICR mice derived from three different sources to ethanol/hydrochloric acid-induced gastric injury

Abstract: Animal models for gastric ulcers produced by physical, pharmacological and surgical methods have been widely employed to evaluate therapeutic drugs and investigate the mechanism of action of this disease. ICR mice were selected to produce this model, even though several mice and rats have been widely used in studies of gastric ulcers. To compare the responses of ICR mice obtained from three different sources to gastric ulcer inducers, alterations in gastric injury, histopathological structure, and inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Among the rodent strains supplied by major providers, C57BL/6 and ICR mice are commonly used for research in aging, toxicology, pathology, and physiology [ 3 9 10 ]. Several studies indicated that RMR differs depending on the strain, gender, weight gain, growth rate, and other conditions derived from genetic and circumstantial variables [ 2 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the rodent strains supplied by major providers, C57BL/6 and ICR mice are commonly used for research in aging, toxicology, pathology, and physiology [ 3 9 10 ]. Several studies indicated that RMR differs depending on the strain, gender, weight gain, growth rate, and other conditions derived from genetic and circumstantial variables [ 2 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies approached the RMR-related analysis from the perspective of feeding, activity, and chemical substance administration, examining the effects of these variables within a strain as well as between strains [ 11 12 13 ]. Recently, studies on Korl mice (a domestic mouse strain) reported that they show similar responses to chemical substances [ 9 14 ]. However, no scientific studies have analyzed the metabolic phenotypes of mice substrains derived from three different origins, especially in C57BL/6Korl and Korl:ICR mice.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological and hematological data values had consistency in the study. Song et al (2016) suggested that three ICR groups, the Korl:ICR, A:ICR and B:ICR derived from different sources have an overall similar response of body weight, histopathological structure and inflammation to gastric ulcer inducers [25]. Alcohol induced ulcer model comparison assessment for reviewing the characteristics of the Korl:ICR were having similar result.…”
Section: Discussionmentioning
confidence: 99%
“…In a genome-wide single nucleotide polymorphism (SNP) analysis, unique genetic variation was identified in Korl:ICR mice when compared with two ICR stocks derived from different sources [ 8 ]. However, Korl:ICR mice showed similar overall responses to gastric ulcers induced by EtOH/HCl administration compared to those in A:ICR and B:ICR mice stocks derived from different sources [ 9 ]. Also, similar responses to loperamide (Lop)-induced constipation in the transverse colon were detected in three ICR stocks (Korl:ICR, A:ICR, and B:ICR) derived from three difference sources [ 10 ].…”
Section: Introductionmentioning
confidence: 99%